2014
DOI: 10.1007/s10895-014-1451-7
|View full text |Cite|
|
Sign up to set email alerts
|

Cetyltrimethylammonium Bromide Capped 9-Anthraldehyde Nanoparticles for Selective Recognition of Phosphate Anion in Aqueous Solution Based on Fluorescence Quenching and Application for Analysis of Chloroquine

Abstract: Cetyltrimethylammonium bromide (CTAB) capped 9-Anthraldehyde nanoparticles (9-AANPs) in aqueous suspension prepared by reprecipitation method are seen brick shaped in Scanning Electron Microscope image. The Dynamic Light Scattering histogram of nanoparticle suspension reveals narrow particle size distribution and average particle size is 89 nm. The positive zeta potential 20.8 mV measured on zeta sizer indicates high level stability of nanoparticle suspension. The blue shift of 65359.47 cm(-1) observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The low emission intensity in solution of isolated molecule is due to dissipation of energy to molecular rotations. The aggregation induced enhanced emission is usually correlated to the restricted intramolecular rotations resulting in decreased non-radiative pathways and enhanced emission [28,33,34]. The formation of nanostructure is further supported by the fluorescence lifetime measured at its emission wavelength 417 nm.…”
Section: Uv-visible and Fluorescence Properties Of N-minpsmentioning
confidence: 86%
See 3 more Smart Citations
“…The low emission intensity in solution of isolated molecule is due to dissipation of energy to molecular rotations. The aggregation induced enhanced emission is usually correlated to the restricted intramolecular rotations resulting in decreased non-radiative pathways and enhanced emission [28,33,34]. The formation of nanostructure is further supported by the fluorescence lifetime measured at its emission wavelength 417 nm.…”
Section: Uv-visible and Fluorescence Properties Of N-minpsmentioning
confidence: 86%
“…The structured, broad absorption band of methyl isatin seen in the region 370-450 nm is reduced appreciably due to aggregation of molecules and a new blue shifted sharp band appeared with maximum at 272 nm is assigned to the nanostructure. The large blue shift in the absorption spectrum of N-MINPs with respect to N-MI in acetone indicate formation of H-type aggregates due to strong lateral -stacking interactions and functional polar C O groups point outward towards aqueous phase [28,32]. The fluorescence spectrum of N-MINPs in aqueous suspension shown in Fig.…”
Section: Uv-visible and Fluorescence Properties Of N-minpsmentioning
confidence: 94%
See 2 more Smart Citations
“…The particle size estimated from the SEM image was 200 nm and relatively greater than the average diameter obtained from DLS histogram. This was due to the agglomeration of the nanoparticles during preparation of thin film on glass substrate for SEM images The reports available in literature on IR‐studies have shown that –C=O in the pyrrolidone ring is very sensitive to hydrogen bond formation with water molecule and hence the polymeric form of vinyl pyrrolidone provided a flexible charged membrane around anthracene colloids .…”
Section: Characterization Of Pvp‐anpsmentioning
confidence: 99%